2023
DOI: 10.24996/ijs.2023.64.12.9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Resistance Genes (Blandm and Blavim) of Escherichia Coli in the Aquatic Environment

Zinah Mohammed Mahdi,
Zainab Hani Hatif,
Mohammed Hassan Younis
et al.

Abstract: The study aims to detect the presence of carbapenems genes and the prevalence of antibiotic-resistant E. coli in the Tigris River. Samples were collected from three sites of the Tigris River: S1Adhamiya, S2 Medical city hospital, and S3 Abu Nuwas. It diagnosed 40 isolates of E. coli out of 67 isolates of bacteria by Vitek2. The antibiotic sensitivity was determined by the disk diffusion method. E.coli isolates were tested against 7 antibiotics these belonged to β-lactam, Carbapenem. Also, the resistance genes)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The results revealed considerable resistance, with E. coli showing high resistance rates to β-lactam antibiotics such as amoxicillin-clavulanic acid (AMC) (82.5%) and piperacillin (PRL) (62.5%). Additionally, the study investigated the presence of carbapenem resistance genes and identified two isolates (5%) with the blaVIM gene and one isolate (2.5%) with the blaNDM gene, emphasizing the potential for carbapenem resistance in the E. coli population [71].…”
Section: Types Of Args In Aquatic Environmentmentioning
confidence: 99%
“…The results revealed considerable resistance, with E. coli showing high resistance rates to β-lactam antibiotics such as amoxicillin-clavulanic acid (AMC) (82.5%) and piperacillin (PRL) (62.5%). Additionally, the study investigated the presence of carbapenem resistance genes and identified two isolates (5%) with the blaVIM gene and one isolate (2.5%) with the blaNDM gene, emphasizing the potential for carbapenem resistance in the E. coli population [71].…”
Section: Types Of Args In Aquatic Environmentmentioning
confidence: 99%